Deep hydrocarbon charging and accumulation in complex fault blocks, the northern part of the eastern Liaohe depression, China - Che Shen; Youlu Jiang; Qiang Guo (Energy Exploration & Exploitation)
Deep exploration in complex fault-block regions is critical for global oil and gas development. As a representative region characterized by complex fault-block development, the northern part of the eastern Liaohe depression poses challenges in understanding the charging time and migration channels of deep hydrocarbons due to its intricate structural and reservoir conditions. For this purpose, this study utilizes diverse geological data from recent explorations, employing the petrological characteristics of inclusions, homogenization temperatures, and simulations of the thermal burial history to investigate the charging times of deep hydrocarbons. It combines the diagenetic processes of the reservoir with tectonic evolution to reveal the charging pathways and dynamic processes of deep hydrocarbons in the northern part of the eastern Liaohe depression. The results indicate that there are two charging periods in the study area: the late Oligocene (32.9–27.5 Ma) and from the late Neogene to the present (8.7–0 Ma). During these critical periods, faults with high activity intensity and low fault section normal stress were in an open state, which can serve as pathways for the vertical long-distance migration of hydrocarbons. In the first charging period, a substantial volume of hydrocarbon expelled from the source rocks migrates vertically into the deep sandstone reservoir through opening faults, exhibiting characteristics of source–reservoir separation. Subsequently, a brief uplift at the end of the Oligocene halted hydrocarbon generation. In the second charging period, as the source rocks further matured, a substantial volume of natural gas was injected into the deep reservoirs. At this period, the faults approached the seal, preventing hydrocarbons from migrating vertically and allowing them to enter the deep sandstone reservoirs adjacent to the source rocks, reflecting characteristics of source–reservoir proximity.